2017
DOI: 10.1128/aac.01369-16
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Agonist GS-9620 Is a Potent Inhibitor of Acute HIV-1 Infection in Human Peripheral Blood Mononuclear Cells

Abstract: GS-9620 is a potent and selective oral Toll-like receptor 7 (TLR7) agonist that directly activates plasmacytoid dendritic cells (pDCs). GS-9620 suppressed hepatitis B virus (HBV) in animal models of chronic infection and transiently activated HIV expression ex vivo in latently infected peripheral blood mononuclear cells (PBMCs) from virally suppressed patients. Currently, GS-9620 is under clinical evaluation for treating chronic HBV infection and for reducing latent reservoirs in virally suppressed HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
1
46
2
Order By: Relevance
“…In addition to TLR9 agonists, TLR7 agonists are also being investigated in HIV cure-related research [41]. The TLR7 agonist GS-9620 induce a pDC-dependent anti-HIV activity in vitro but also leads to an increase in the proinflammatory cytokines such as IL-6 [42]. Interestingly, a recent nonhuman primate study suggested that the TLR7 agonist GS-986 in combination with Ad26/MVA vectored therapeutic simian immunodeficiency virus vaccination improved immunologic control and delayed viral rebound compared to placebo-treated animals whereas animals receiving GS-986 alone appeared to have no improvement in virological control or change in the size of the viral reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TLR9 agonists, TLR7 agonists are also being investigated in HIV cure-related research [41]. The TLR7 agonist GS-9620 induce a pDC-dependent anti-HIV activity in vitro but also leads to an increase in the proinflammatory cytokines such as IL-6 [42]. Interestingly, a recent nonhuman primate study suggested that the TLR7 agonist GS-986 in combination with Ad26/MVA vectored therapeutic simian immunodeficiency virus vaccination improved immunologic control and delayed viral rebound compared to placebo-treated animals whereas animals receiving GS-986 alone appeared to have no improvement in virological control or change in the size of the viral reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GS-9620 is able in vitro to inhibit HIV-1 infection in human peripheral blood mononuclear cells [151]. It was also demonstrated that GS-9620 induced HIV RNA expression ex vivo in PBMC isolated from patients on suppressive antiretroviral therapy [152e154].…”
Section: Pyrimidine and Purine Base Derivativesmentioning
confidence: 99%
“…Some novel methods and therapeutic strategies that can overcome viral latency have been developed such as HDAC, disulfiram, galectin-9, ingenol-3-angelate, prostratin, 5-azadC, bryostatin-1, and Runx1 [100, 101]. TLR7/8 agonists induce production of IFN-α that effectively inhibits HIV-1 replication in activated lymphocytes, macrophages or latently infected monocytic cell lines [102, 103]. Because HIV eradication is not achieved by highly active antiretroviral therapy, a strong rationale to investigate the curative potential of IFN-α is needed.…”
Section: Current Potential Applications Of Type I Ifn Classesmentioning
confidence: 99%